Togaf Analysis in Bengkalis State Polytechnic Laboratory Information Systems Design - Suhada, Khairus; Agustin, Wirta; Rahmaddeni; Rio, Unang (P3M Politeknik Negeri Bengkalis, 2025)
Laboratories in educational institutions have an important role in supporting learning and research. However, effective and efficient laboratory management is still a challenge, especially in recording inventory and managing consumables (BHP). The Bengkalis State Polytechnic Informatics Engineering Laboratory already has an application system, but there are still limitations in recording monthly BHP usage, borrowing facilities, and proposing equipment procurement. This research aims to design a blueprint for an integrated laboratory information system using The Open Group Architecture Framework (TOGAF) Architecture Development Method (ADM). This approach is applied to phase F: Migration Planning, which includes requirements analysis, business architecture design, information system architecture, as well as strategy and migration implementation. The results of this research produce a blueprint for a system information laboratory that includes application design, technology recommendations, and implementation stages that can be used as a guide in system development. This blueprint is expected to increase laboratory management efficiency by optimizing inventory recording, procurement planning and maintenance of laboratory services. In addition, the TOGAF ADM approach used can be adapted for laboratories in other educational settings that have similar needs.